PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DI INDONESIA: SEBUAH TINJAUAN LITERATUR SISTEMATIS - Ahmad Sulaiman; Siti Azizah (PEDAGOGIK : JURNAL PENDIDIKAN, 2020)
There is an assumption stating that the Problem-Based Learning (PBL) approach and critical thinking skills are not compatible with the context of Indonesian education. To answer that assumption, this systematic literature review verifies the effectiveness of PBL in honing the critical thinking skills of Indonesian students based on previous studies. This systematic review also examines the extent to which the research results are supported by appropriate research frameworks and methodologies. Searching for all research in reputable online databases with relevant keywords was carried out to obtain all studies within a span of ten years (2009-2018) that used PBL to evaluate or observe changes in students' critical thinking capacities. There are twenty studies that meet the inclusion criteria and are the material of analysis in this systematic literature review. Although almost all studies (n = 17) reported that PBL was effective in encouraging critical thinking skills, they did not have a clear variable framework and weak research design. In these studies, the PBL concept was very varied and the measurement instruments were not well constructed. This systematic review concludes that further research methodologically stronger and based on key and current literature is urgently needed. The studies will build sufficient support from the scientific community and practitioners to adopt PBL and think critically as paradigms and learning outcomes in Indonesia.